Biological features of dairy cattle and increasing the efficiency of its breeding in the context of livestock intensification in the Yaroslavl region - R. V. Tamarova; E. I. Ukhov (Аграрная наука Евро-Северо-Востока)
The purpose of the research is to establish the most effective methods of breeding dairy cattle for working with the herd in the future. The research was conducted according to the data of zootechnical and breeding records. The object of the research were 286 cows and 7 sires of two Holstein lines: Vis Back Ideal and Reflection Sovering. The following indicators of daughter productivity were analyzed for the first lactation: milk yield for 305 days of lactation, mass fraction of fat, mass fraction of protein in milk, as well as the sum of milk fat and protein in kg, also daughters were compared with mothers and peers. Correlations and heritability of productivity traits in mother-daughter pairs have been determined. Good adaptability of Mikhailovsky type of cows of the Yaroslavl breed, a positive effect of breeding under intensive technology conditions at a dairy complex have been established. The best sires for future breeding have been identified. In addition, the results of the BLUP assessment of these sires in breeding farms of the Russian Federation conducted at VNIIplem are reflected. At the same time, the best stud bull, a prepotent improver of daughters' milk productivity, Tracer 3125479393, with a high breeding effect on a set of quantitative and qualitative indicators, was identified. It is advisable to use it in re-selection for the improvement of dairy cattle. It has been established that the actual indicators of daughters are quite high: from 7764 kg to 8777 kg in milk yield, from 3.87 to 4.08 % in MFF (Milk Fat Fraction) and from 3.34 to 3.66 % in MPF (Milk Protein Fraction). Daughters significantly surpass their mothers in milk yield from 1348 kg to 2399 kg (Р≤0.01)) and in protein – 0.17 to 0.66 % (Р≤0.01); in terms of milk fat content, they are significantly inferior to mothers – from -0,1 to -0.43 % (Р≤0.1). The total content of milk fat and protein in kilograms is also higher in daughters than in mothers – from 16.6 to 41.1 % (Р≤0.01).